Clinical and laboratory manifestations of childhood and adult-onset systemic lupus erythematosus in Cipto Mangunkusumo Hospital - Syarif Faisal; Arwin Akib; Taralan Tambunan (Paediatrica Indonesiana, 2003)
Background Childhood-onset SLE is more severe than the adult type.Objective To compare the clinical and laboratory manifestationsof childhood- and adult-onset systemic lupus erythematosus (SLE).Methods A retrospective study on child and adult SLE patientswas conducted in the Division of Pediatric Allergy and Immunol-ogy, Department of Child Health and Department of Internal Medi-cine, Medical School, University of Indonesia/CiptoMangunkusumoHospital (FKUI/RSCM) Jakarta.Subjects One hundred and twenty-nine subjects met the studycriteria consisting on 54 childhood- onset (41.9%), 75 adult-onset(58.1%), and 122 (94.6%) females and 7 (5.4%) males from Janu-ary 1995 until December 2000.Results Fever, arthralgia and vasculitis were the most frequentsigns found in both childhood-onset and adult-onset SLE. The liver,spleen, lymph nodes, cardiovascular, gastrointestinal tract, andeyes were the organs involved and significantly had a larger pro-portion in the childhood-onset. Decrease of C3 was more frequentlyfound in the childhood-onset. Out of 17 childhood-onset patientswho died, 13 died at the age of 0-11 year-old. Two of the adult-onset patients also died.Conclusion Childhood-onset SLE had some different character-istics compared to adult form